Mobile business intelligent center (MBIC) - Abd. Jalil, Rohaizan (2007)
There are many competitors in the entrepreneur world. Without having a good knowledge and skill development in entrepreneurship our government mission and objective to groom Malay economic will be impossible. There is the way to solve all kind of problem face about registration program and taking course within this service. The rising of mobile technology using the SMS give an advantage to entrepreneur development skills. The MBIC are the one of the services provide to solve the problem in entrepreneurs world for make a registration in entrepreneurs development program to polish their skill and knowledge in the competative business world. Briefly, this service is to make sure entrepreneur to take the program depend on their interest and their business itself. The process for develop this service are using Unified Modeling Language (UML). The reason is to make it easy to develop for this project more effectively. In addition, mobile technology that are arise also facilitate to make this system more convenient to develop, MySQL and Phynton programming language is a few of example as a back bone for this system development. Business plan discusses what marketing and financial strategies in commercializing the system at later stage. Consequently this service give some opportunity to entrepreneur and the SMS technology itself to give a compliment for each other. Last but not least, SMS can give more advantages among entrepreneur community to develop their competitive age in the real world business strategy